Analisis Wacana Teun A. Van Dijk Pada Film Dokumenter Sexy Killer - Fauzannur Ramadhan; Achmad Herman (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2021)
This research sees that power is constructed through a discourse strategy based on Teun A. Van Dijk's discourse analysis. Through a qualitative descriptive method, this discourse analyzes the level of text, social cognition, and social film context. The subject of the research is the Sexy Killers film, with the object of research are scene that showed power. The results of the study found that power is constructed through the upper and lower classes of the film and the role of the narrator who tends to limit the audience's interpretation space. In text analysis, power is represented to discredit certain political elites. At the level of social cognition, this film is produced based on the documentary genre which is investigative and identically accommodates the voices of the lower class people who are rarely reported by the media. Meanwhile, at the social context level, the discourse that comes through the form of control is in a persuasive form, which has led to a social movement in the form of a review of the Sexy Killers film which was held in several cities in Indonesia. Based on the discourse presented in the film, implicitly forming a skeptical and cynical view of politicians or the government.